A highly regio‐ and stereoselective selenoxide elimination of 1, 2‐bis[4‐(trimethylsilyl)phenylseleno]alkanes to give (E)‐alkenyl selenoxides and its mechanistic study. Issue 2 (12th February 2016) - Tarao, Asami; Niki, Aya; Komagawa, Shinsuke; Arimitsu, Kenji; Uchimoto, Hitomi; Kawasaki, Ikuo; Yamaguchi, Kentaro; Nishide, Kiyoharu
Abstract: The elimination of a 2‐substituted selenoxide is known to provide a variety of different products, which are largely dependent on the nature of the substrate and its substituents. Oxidation of ( Z )‐1, 2‐bisarylseleno‐1‐alkenes lead to formation of bisselenoxide intermediate, which gives the corresponding alkynyl selenide by anti ‐elimination and subsequent reduction by the ArSeOH byproduct. In this study, the selective elimination of selenoxide from 1, 2‐bis[4‐(trimethylsilyl)phenylseleno]alkanes resulted in the exclusive formation of ( E )‐alkenyl selenoxides via a 1, 2‐bisselenoxide intermediate. The oxidation of 1, 2‐bis[4‐(trimethylsilyl)phenylseleno]alkanes with one equivalent of meta ‐chloroperoxybenzoic acid resulted in the non‐selective formation of several arylseleno alkene derivatives, and it was subsequently shown that the elimination of the corresponding 1, 2‐bisselenoxide proceeds with high regio‐ and stereoselectivity. Mechanistic investigations for this unique elimination have been performed with 77 Se NMR experiments and computational studies. Abstract : The oxidation of 1, 2‐bis(arylseleno)alkanes using two equivalents of meta ‐chloroperoxybenzoic acid proceeded via bisselenoxide intermediate to afford ( E )‐1‐arylseleninyl‐1‐alkenes with high regio‐ and stereoselectivity. The selectivity was studied by 77 Se NMR experiment and the computational calculations.